Determinasi Religiusitas, Kecerdasan Emosional, dan Dukungan Sosial terhadap Kecemasan Akademik Siswa - Ely Roy Madoni; Abidatul Mardliyah (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2021)
Anxiety is a mixed feeling that contains feelings of fear and concern with no known cause for experiences or events that have not yet occurred. The greatest anxiety often occurs when students face academic demands and assignments. The research focuses on answering the problem of whether there is a correlation between religiosity, emotional-intelligence and social-support with students' academic anxiety. The research subjects were students of SMK Negeri X Jombang who were taken in a proportional stratified manner. The research data were collected using four instruments, namely the religiosity scale, emotional intelligence scale, social support scale and anxiety scale. The analysis of the research data used was multiple regression and partial correlation. The results of the study proved that religiosity, emotional intelligence, and social support contributed 10.7% to students' academic anxiety. Thus 89.3% of anxiety is influenced by other variables. Students are expected to be able to increase religiosity in everyday life and to know and direct all the weaknesses and strengths in themselves. As well as having the ability to establish positive social relationships with the environment around them. Keywords: religiosity; emotional-intelligence; social-support; academic-anxiety